2019
DOI: 10.1111/eufm.12232
|View full text |Cite
|
Sign up to set email alerts
|

Motivated monitoring by institutional investors and firm investment efficiency

Abstract: We find that motivated monitoring by institutional investors mitigates firm investment inefficiency, estimated by Richardson's (2006) approach. This relation is robust when using the annual reconstitution of the Russell indexes as exogenous shocks to institutional ownership during the period 1995–2015 and after classifying institutional ownership by institution type. We also show that closer monitoring mitigates the problem of both over‐investing free cash flows and under‐investment due to managers’ career con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 79 publications
3
19
0
Order By: Relevance
“…The negative association of institutional ownership with investment efficiency is consistent with Cook et al (2019), who argue that institutional ownership has a negative relationship with under-investment and a positive association with overinvestment, which shows the inefficiency of investment. Ward et al (2020) argued that institutional ownership characteristics are not homogenous. Their monitoring role depends on the institution's type, investment horizons, and trading preferences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The negative association of institutional ownership with investment efficiency is consistent with Cook et al (2019), who argue that institutional ownership has a negative relationship with under-investment and a positive association with overinvestment, which shows the inefficiency of investment. Ward et al (2020) argued that institutional ownership characteristics are not homogenous. Their monitoring role depends on the institution's type, investment horizons, and trading preferences.…”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that, in the case of institutional ownership, the firm could eliminate financial constraints. Rare opportunities for investment tend to overinvest, consequently failing to achieve the optimal investment level or efficiency (Ward et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of those factors is the lack of firm-specific information in less developed economies (Ebrahimnejad & Hoseinzade, 2019), making it hard to evaluate the true longterm significance of that company (Porter, 1992). Institutional investors' capabilities are limited to monitoring each firm in their portfolios' capabilities and monitoring each firm in their portfolios (Ward, Yin, & Zeng, 2020). Therefore, institutions use information related to firm performance and current corporate earning that is easily accessible.…”
Section: Pressure-sensitive Institutions and Research And Development Intensitymentioning
confidence: 99%